SOCIAL DETERMINANT OF STUNTING AMONG UNDER FIVE CHILDREN - Sari Priyanti; Agustin Dwi Syalfina (Jurnal Kebidanan, 2018)
Stunting is condition of nutritional status based on length for age or height for age with Z-score value that equal to or less than minus two standard deviation (-2 SD). Therefore, the purpose this study to analyze the factors affecting of stunting. This cross sectional study done in Dlanggu primary health care. Sample taken with simple random sampling technique amounted to 88 respondents. Colectting data with check list and questionnaire or analyze with chi square and logistic regression. Result of bivariat shows length of born (PR=1,676; 95%CI=1,060-2,651), family income (PR=2,333; 95%CI=1,297-4,199), size of upper arm circumfence of the mother (PR=2,288; 95%CI=1,492-3,508), and complication of pregnant (PR=2,154; 95%CI=1,297-3,578) was risk factor of the stunting in children under five years. The most factor has influenced of stunting based on multivariate thas education of mother, family income and complication of pregnant. Prevention of stunting with successful movement of the first 1000 days of life through improved mutrition of pregnant, given exclusive breast feeding and balanced nutrition in the family.